Postoperative Chylous Ascites in Patients With Gynecologic Malignancies. Issue 2 (1st February 2012) - Han, Duo; Wu, Xiaohua; Li, Jin; Ke, Guihao
Abstract : Objective: To evaluate the incidence and the effective treatment of postoperative chylous ascites in patients with gynecologic malignancies. Methods: In this report, we retrospectively reviewed the cases of 4119 patients who underwent pelvic and/or para-aortic lymph node dissection for gynecologic malignancies in Fudan University Cancer Hospital. Results: Among these 4119 cases, 7 (0.17%) patients had chylous ascites postoperatively. The average age of these patients was 52 years. The mean time interval between operation and the appearance of chylous ascites was 30 days (range, 5–75 days). The incidence of chylous ascites after para-aortic lymphadenectomy was approximately 0.32% (5/1540), whereas the rate after pelvic lymphadenectomy alone was 0.077% (2/2579). All cases with chylous ascites were resolved by conservative treatment. This included placement of a peritoneal drainage tube. The mean time to resolution was 13 days (range, 2–28 days). None of the cases had recurrent chylous ascites during follow-up. Conclusions: Para-aortic lymph node dissection may be associated with postoperative chylous ascites. Patients may have their chylous ascites successfully treated with conservative management. An abdominal drainage tube can be a simple and effective approach and should be considered in the treatment.